Adolescentes de classes populares e o mercado de trabalho : a experiência do Programa Correios Educação para o Futuro - Monteiro, Gilberto Maximiliano (2007)
In this research we present a Program of Education inside directed toward the world of the developed work of a Public company ECT (Brazilian Company of Post offices and Telegraphs), whose objective was to promote actions that assured the indispensable acquisition of habits, experiences and attitudes to the adjustment in the productive work and the social convivência of deriving adolescents of families of popular classrooms. The procedures of act of contract are described, prerequisite for ingression, remuneration, benefits, definition of the activities, rights and duties, training, partner-educative activities, pertaining to school accompaniment. We stand out the paper of the people who orientates whose responsibility was to follow and to instruct the young during its hours of working. This set of action had as purpose, to search the occured transformations in the adolescents who had participated of the project and to analyze if the objectives considered for the program they had reached its goals, as well as pointing ways that can give to continuity the situations of the same nature.